Model Peran Berbagai Jenis Pasar terhadap Pertumbuhan Ekonomi - Simanjuntak, Elliviana; Pintauli, Rolyana Ferinia (Fakultas Ekonomi Universitas Advent Indonesia, 2026)
The market is a factor in the continuity of economic growth to improve people's welfare. Some types of markets are, monopsony, monopoly, oligopoly, and oligopsony which have different characteristics in transaction activities between buyers and sellers. Traditional markets help the community by providing efficient prices and helping the development of small traders' businesses. The research method is an approach carried out to collect and analyze, which begins with a thought that forms a problem formulation so that it gives rise to an initial hypothesis, assisted by research understanding, so that research can be analyzed which produces a conclusion. The theory of economic growth explains the importance of the readiness of physical, human, and government capital that supports economic growth so that it can run well and have a long term. However, the existence of market failures such as monopolies and externalities shows the need for government power to maintain efficiency and justice in it.